Faktor-faktor yang Memengaruhi Minat Petani Kelapa Sawit Rakyat terhadap Sertifikasi RSPO di Kecamatan Bosar Maligas - Tifany Zia Aznur; Khairul Fahmi Purba; Dian Retno Intan; Azqia Wardani; Hendris Syah Putra (Universitas Galuh, 2026)
Being an export commodity, palm oil must meet global standards in order to compete and be accepted in international markets. One of the standards that must be met is the sustainability standard through the Roundtable on Sustainable Palm Oil (RSPO). The RSPO aims to ensure that palm oil production is carried out in an environmentally friendly manner and does not harm social and economic aspects. The RSPO principles state that palm oil production must protect the environment and biodiversity, safeguard social, community, and labor interests, and increase food availability. This study aimed to analyze the factors that influence smallholder palm oil farmers' interest in RSPO certification in Bosar Maligas District. The study used a survey method with a total sample of 342 people, consisting of 161 RSPO-certified farmers and 181 non-RSPO farmers, selected using stratified random sampling. The data were analyzed using econometric procedures, namely binary logistic regression. The results showed that the four factors, farmer age, education, number of dependents, and farming experience, have a positive and significant effect on farmers' interest in RSPO certification in Bosar Maligas District, with a contribution of 32.1%. Furthermore, it is necessary to develop a certification program through group-based assistance so that the RSPO certification adoption process can be more effective.